MỤC LỤC
Xét $\large \int\limits_{0}^{1} (x + 1) e^{x^{2} + 2x} \mathrm{d}x$ nếu đặt $\large t = x^{2} + 2x$ thì $\large \int\limits_{0}^{1} (x + 1) e^{x^{2} + 2x} \mathrm{d}x$ bằng
Lời giải chi tiết:
Ta có $\large t = x^{2} + 2x \to \mathrm{d}t = (2x + 2)\mathrm{d}x \to (x + 1)\mathrm{d}x = \dfrac {\mathrm{d}t}{2}$
Đổi cận $\large x = 0 \to t = 0; x = 1 \to t = 3$
Ta được $\large \int\limits_{0}^{1} (x + 1) e^{x^{2} + 2x} \mathrm{d}x = \int\limits_{0}^{3} e^{t} \dfrac {\mathrm{d}t}{2} = \dfrac {1}{2} \int\limits_{0}^{3} (t + 1) e^{t} \mathrm{d}t$
Xem thêm các bài tiếp theo bên dưới